Strategies For Empowering Women Farm Workers To Increase Income Through Weed Processing Training - Priska Febiola Sekaryahya; Solehudin; Nadeak, Banuara (Jurnal Sosial Humaniora, 2024)
Women farm workers are an economically vulnerable group of rural communities. The majority of them live below the poverty line with low and uncertain incomes. This research aims to develop innovative strategies to increase the income of women farm workers through the use of weeds as raw materials for processed products of economic value. Through a research and development approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), this research produced several important findings. First, identified types of weeds that are abundant in agricultural land and have the potential to be processed into products of economic value such as processed food, organic fertilizers, and herbal medicines. Second, a comprehensive weed processing training module was developed in accordance with the needs and characteristics of women farm workers, covering aspects of production, packaging, marketing, and business management. The results showed an increase in knowledge, skills, and motivation of women farm workers in entrepreneurship through the use of weeds after participating in the training program, with an average increase in pre-test and post-test scores of 36.15 points. In addition, there was an increase in the income of women farm workers who participated in the training program and ran a weed processing business, with an average income of Rp 890,000 per month, compared to before the training where they had no income from the weed processing business. This study concludes that the use of weeds into products of economic value is an effective strategy to increase the income and welfare of women farm workers and their families. The training and mentoring model with the ADDIE approach has proven successful in equipping women farm workers with entrepreneurial knowledge and skills. This finding implies that similar models can be applied more broadly to empower groups of women farmworkers in various parts of Indonesia.